PENGARUH MEDIA AUDIO VISUAL TERHADAP KEMAMPUAN MENYIMAK BAHASA INGGRIS SISWA KELAS IV SEKOLAH DASAR - Dadan Setiawan; Ghina Nur’aini; Sakirah; Vanesa Anjani (Jurnal Lensa Pendas, 2024)
The aim of this research is to analyze the influence of audiovisual media on the English listening skills of class IV students at SDN 1 Kalikoa. This research approach is quantitative. This research method is quasi-experimental. This research design uses a non-equivalent pretest posttest control group design. The population of this research was 42 class IV students at SDN 1 Kalikoa. The sample for this study was 21 students in the experimental group and 21 students in the control group. This research sampling was not carried out randomly. This research data was collected through tests. A total of 10 multiple choice questions and 2 essay questions were given to see students' listening abilities. This research data was analyzed statistically with the help of SPSS version 25 for Windows. Research findings show that students' English listening skills have improved significantly after learning with audiovisual media. This means that audio-visual learning media has a significant influence. This is known from the sig value = <0.05. Audio-visual learning media has a positive impact on students' listening abilities